Cross-Informant Assessment of Children's Sympathy: Disentangling Trait and State Agreement - Zuffianò, Antonio; Sette, Stefania; Colasante, Tyler; Buchmann, Marlis; Malti, Tina (Frontiers in Applied Mathematics and Statistics, 2018)
The use of multiple informants (e.g., caregivers and teachers) is recommended to obtain a comprehensive profile of children’s social emotional development. Evidence to date indicates that only a small-to-moderate degree of convergence exists between different informants’ assessments of children’s social-emotional functioning, especially when the contexts of such informants’ observations are also different. However, whether caregivers and teachers primarily disagree about children’s dispositional emotional tendencies or situational emotional fluctuations remains unclear. In this study, we investigated the extent to which caregivers and teachers converged in their evaluation of children’s dispositional and state sympathy (i.e., a relatively internal and low visibility emotional response of concern for another’s wellbeing) in a nationally representative sample of Swiss children (N = 1,273) followed from 6 to 12 years of age. Using analyses based in latent state–trait theory, we found that caregivers and teachers showed moderate-to-large agreement (r = .510) at the dispositional, trait level of children’s sympathy, but only a small level of agreement in their assessments of children’s situational, state-like manifestations of sympathy (r = .123). These findings highlight the differential convergence of adults’ ratings of one core dimension of children’s social-emotional development, i.e., sympathy, at the dispositional and situational levels, and, relatedly the need to investigate the reasons behind discrepancies at both levels of analysis. We elaborate on practical implications for designing social-emotional screening tools across different informants and contexts.